Active Power Filter DC Bus Voltage Piecewise Reaching Law Variable Structure Control. (2nd September 2014) - Liu, Baolian; Ding, Zujun; Zhao, Huanyu; Jin, Defei
Abstract : The DC bus voltage stability control is one key technology to ensure that Active Power Filter (APF) operates stably. The external disturbances such as power grid and load fluctuation and the system parameters changing may affect the stability of APF DC bus voltage and the normal operation of APF. The mathematical model of DC bus voltage is established according to power balance principle and a DC bus voltage piecewise reaching law variable structure control algorithm is proposed to solve the above problem, and the design method is given. The simulation and experiment results proved that the proposed variable structure control algorithm can eliminate the chattering problem existing in traditional variable structure control effectively, is insensitive to system disturbance, and has good robustness and fast dynamic response speed and stable DC bus voltage with small fluctuation. The above advantages ensure the compensation effect of APF.